NBP0702 surface sediment sample information and images - Leventer, Amy; Jacobs, Stanley (U.S. Antarctic Program (USAP) Data Center, 2021)
This dataset contains images and field description of Smith-McIntyre sediment grab samples from Expedition NBP0702 between the Ross Sea and the Amundsen Sea.